ANALISIS REAKSI PASAR ATAS PERISTIWA PENGUMUMAN DIVIDEN TERHADAP ABNORMAL RETURN SAHAM PERUSAHAAN OTOMOTIF DI BURSA EFEK INDONESIA - Bayu Wijayantini (SEGMEN Jurnal Manajemen dan Bisnis, 2015)
This study aimed to analyze the market's reaction to abnormal stock returns before and after the dividend announcement during the observation period on Automotive companies are listed in the Indonesia Stock Exchange . Of the 12 -listed company , elected five companies that meet the criteria . Analysis of the results showed that the results of t value of 3.046 , with ap value of 0.006 . So it can be stated that there is a difference of abnormal stock returns before the announcement of the dividend after the dividend announcement . Individually there is increase in price per share after dividends. This increase is assumed that the event dividend responded well by investors and give a positive signal for the company Keywords: abnormal return.